Evaluation of Storytelling Learning - Andi Sulfana Masri; Agus Nuryatin; Subyantoro Subyantoro; Mukh. Doyin (Universitas Negeri Semarang, 2022)
Evaluation of storytelling learning is important to assess the success of speaking learning management. Speaking skills are important for everyday life. This study aims to describe the evaluation of storytelling learning in class VII. The type of research used in this research is qualitative research. This learning evaluation will refer to the Goal Oriented Evaluation Model micro-scale evaluation model initiated by Ralph W. Tyler. The subjects of this study were Indonesian language teachers and class VII students at SMP Negeri 33 Makassar totaling 32 people. Data was collected using test and non-test techniques. The data analysis technique used is an interpretive technique. The result of this research is that the storytelling learning program in class VII SMP Negeri 33 Makassar is successful. Thus, it is hoped that the results of this study can be useful in the implementation of storytelling learning in other schools.